Infant herpes zoster: a 10-year retrospective study (Research, Society and Development, 2022)
Introduction: The Varicella-Zoster Virus (VVZ) produces two clinical forms: Varicella and Herpes Zoster (HZ). Chickenpox is an acute illness associated with systemic symptoms and a rash that progresses to blisters and crusts. It is usually benign in children, but in adults it can lead to pneumonia or encephalitis, permanent sequelae, and death. Objectives: To analyze the prevalence of HZ and the clinical characteristics of cases treated at a referral hospital in the city of Fortaleza - CE during the years 2009-2019. Methods: Retrospective, cross-sectional and descriptive study that aims to analyze the medical records of pediatric patients who were treated at the Hospital São José de Diseases Infectious from 2009 to 2019. Discussion: It is known that HZ is a relatively frequent disease in the population, affecting several individuals at some point in their lives. Of this total, up to 3% require hospitalization. Although most cases are cured in a few weeks, the clinical picture can evolve with severe manifestations and complications, prolonging hospitalization time, generating more morbidities and higher costs to the health system. Conclusion: Given this scenario, it is important to know the profile of patients diagnosed with HZ due to the complications of the disease, which can have a great impact on quality of life, so that health promotion and intervention actions, such as vaccination against zoster, currently only available on the private network, may become increasingly frequent and available to the entire population.